Penerapan Ontology Berbasis Protégé Untuk Mengestimasi Nilai Ekonomi Cryptocurrency - Muhammad Ashardiansyah Putra; Ferdiansyah Ferdiansyah; Linda Atika; Kiky Rizky Nova Wardani (Journal of Information Technology Ampera, 2021)
Cryptoccurency is a digital currency that is used as a medium of exchange as well as rupiah and dollars. And just like currency, Cryptocurrency also experiences value volatility or commonly reffered to as fluctuation. The purpose of this study is to estimate the fluctuating cryptocurrency value by implementing it into ontology using protégé tools. With the ontology, it can make it easier for users to find information about cryptocurrency. The results of this study indicate that ontology is one of the bases of Knowledge Managament Systems which can make it easier to systematizem, improve and accelerate knowledge management so that it is easy to understand for cryptocurrency users. Another result of this research is the creation of an ontology cryptoccurency with the blockchain subclass, users, currency, economu and factors. Each of these subclasses has more subclasses in a structured manner, and the results of making computer technique ontology in estimating the economic value of cryptocurrency are useful for users or people who want to find out more information about cryptocurrency.